STUDI ETNOGRAFI PENDIDIKAN PADA SMA NEGERI 1 UBUD BALI: KONSEP AJEG BALI (HINDU) BERBASIS IDEOLOGI TRI HITA KARANA - Sukadi Sukadi (LPMPP Universitas Negeri Yogyakarta, 2007)
This article concerns a research aimed at explainingideology was ......._A................'.......a staterelevant educational programs in the course shaping ageneration of modern students still retaining the Balinese character.The research was an educational ethnographical one, llSillginformants selected purposively by means of a snowball samplingtechnique. The data, collected by making observationsinterviews, studying compiled documents, and giving tests tostudents, were analyzed qualitatively. The results of the researchindicate that the school above is a school with Hindu nuances and,relevant with its vision, mission, and goal, has developed certaineducational programs to participate in making a success of the moralmovement in the Balinese society to actualize a Bali remainingBalinese.The movement to remain Balinese was defined by theteachers and students as a moral one made to retain the Balinesepeople's characteristic religious and socio-cultural living, preservedon the basis of the implementation of tri hita karana values.Accordingly, the school has developed educational programsempowering students in taking part in actualizing those values atschool, not meaning that the school has abandoned the nationaleducational vision, mission, and goal.